Kad Hari Raya - Noor, Mohd. Yunus; Noor, Azlina; Mohd. Yunus, Mohd. Rosli; Mohd. Yunus, Mohd. Farid; Mohd. Yunus, Mohd. Kamal
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada Mohd Yunus Noor, Noor Azlina, Mohd. Rosli, Mohd. Farid dan Mohd Kamal